2017
DOI: 10.3389/fpls.2017.00748
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CdDHN4, a Novel YSK2-Type Dehydrin Gene from Bermudagrass, Responses to Drought Stress through the ABA-Dependent Signal Pathway

Abstract: Dehydrin improves plant resistance to many abiotic stresses. In this study, the expression profiles of a dehydrin gene, CdDHN4 , were estimated under various stresses and abscisic acid (ABA) treatments in two bermudagrasses ( Cynodon dactylon L.): Tifway (drought-tolerant) and C299 (drought-sensitive). The expression of CdDHN4 was up-regulated by high temperatures, low temperatures, drought, salt and ABA. The sensitivity of CdDHN4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 58 publications
3
25
0
1
Order By: Relevance
“…Further, increased expression of DHN was reported by Kumar et al (2014) in rice and Kosová et al (2014) in barley and wheat under salt, drought and cold stresses. Interestingly, many DHNs have been identified in plants including Arabidopsis thaliana and wheat that are up-regulated by exogenous ABA under drought stress ( Lv et al, 2017 ). Richard et al (2000) reported exogenous application of JA leads to increase in DHN expression in white spruce.…”
Section: Discussionmentioning
confidence: 99%
“…Further, increased expression of DHN was reported by Kumar et al (2014) in rice and Kosová et al (2014) in barley and wheat under salt, drought and cold stresses. Interestingly, many DHNs have been identified in plants including Arabidopsis thaliana and wheat that are up-regulated by exogenous ABA under drought stress ( Lv et al, 2017 ). Richard et al (2000) reported exogenous application of JA leads to increase in DHN expression in white spruce.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, transcription analysis of creeping bentgrass and annual ryegrass showed that plenty of genes were involved in drought response, and the differentially expressed genes were related to energy metabolism, antioxidants, stress defense, photosynthesis and signaling processes [99,100]. Furthermore, a dehydrin gene in bermudagrass CdDHN4 was obtained, which was regulated by an ABA-dependent signaling pathway to enhance the drought tolerance of bermudagrass [101]. In addition, a number of quantitative trait loci (QTL) related to drought stress were identified in creeping bentgrass [102].…”
Section: Drought Stressmentioning
confidence: 97%
“…Overexpression of the Solanum habrochaites dehydrins ShDHN enhances transgenic tomato tolerance to multiple abiotic stresses (Liu et al, 2015). Most dehydrins are distributed along with several ubiquitous dehydration-stress response protein types in plants (Bao et al, 2017; Fan et al, 2017). However, some dehydrins were also found distributed in the vegetative tissues of plants grown under normal conditions, which suggested that the dehydrins may play important roles in the plant growth.…”
Section: Introductionmentioning
confidence: 99%